2009
DOI: 10.1007/s00415-009-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis patients—benefit-risk preferences: Serious adverse event risks versus treatment efficacy

Abstract: Medical interventions carry risks of adverse outcomes that must be evaluated against their clinical benefits. Most MS patients indicated they are willing to accept risks in exchange for clinical efficacy. Patient preferences for potential benefits and risks can assist in decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
98
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 36 publications
10
98
1
3
Order By: Relevance
“…In addition, the incremental improvement in survival was one-and-a-half times as important as an approximate 15%-20% versus 0% risk of having severe nausea and vomiting, fatigue, diarrhea, or sensory neuropathy. The finding of the high relative importance of improved efficacy is consistent with previous conjoint analyses of medical therapies 13,14 and a review of previous literature, 15 which found that patients are willing to accept the risk of serious adverse events in exchange for improved efficacy. For example, Johnson et al 12 evaluated the treatment perceptions among patients with multiple sclerosis, and they found that most patients indicated they are willing to accept risks of life-threatening adverse events in exchange for improvements in their health outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, the incremental improvement in survival was one-and-a-half times as important as an approximate 15%-20% versus 0% risk of having severe nausea and vomiting, fatigue, diarrhea, or sensory neuropathy. The finding of the high relative importance of improved efficacy is consistent with previous conjoint analyses of medical therapies 13,14 and a review of previous literature, 15 which found that patients are willing to accept the risk of serious adverse events in exchange for improved efficacy. For example, Johnson et al 12 evaluated the treatment perceptions among patients with multiple sclerosis, and they found that most patients indicated they are willing to accept risks of life-threatening adverse events in exchange for improvements in their health outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, improved convenience has been found to be influential in treatment choices in other studies. 13,14 For example, in a study of patients with idiopathic thrombocytopenic purpura, patients were willing to accept significant treatment-related risks in exchange for improvements in treatment efficacy and convenient administration. 13 Our study was not without limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, MAR is the increase in treatment risk that exactly offsets the therapeutic benefit of a given improvement in treatment outcomes and indicates the maximum level of treatment-related risk that subjects are willing to accept for a given improvement in disease symptoms or outcomes. 14,19 In the present study, gastroenterologists' MARs were calculated for 6 treatment benefit (efficacy) levels (e.g., severe symptoms to remission, severe symptoms to mild symptoms) for each of the 3 hypothetical patient profiles and each of the 3 potentially fatal SAEs. Additionally, gastroenterologist and middle-aged patient MARs were calculated for each SAE for 2 levels of improvement in symptom severity: from severe to moderate symptoms and from moderate symptoms to remission.…”
Section: Discussionmentioning
confidence: 99%
“…In the practice of DCEs, respondents are presented with a sequence of choices for alternative options and are asked to select the one they prefer, with each alternative being described by different attributes and attribute levels [6][7][8][9]. A recent review showed a substantial increase in the application of DCEs in health economics and medical decision making and a desire to incorporate patients' and doctors' preferences in the study of effectiveness of treatments [10].…”
Section: Introductionmentioning
confidence: 99%